Draft Annual Development Plan of Madhya Pradesh 1968-69 - Planning Commission (Planning Commission, 1967)
According to the 1961 Census, the population of Madhya Pradesh is 3.24 crores. It is the biggest State of the Indian Union in area and has a predominantly agricultural economy. It possesses vast mineral, forest and hydal resources, but it is one of the under-developed States of the country large because its natural resources have remained untapped owing to lack of funds and a very large population of scheduled tribes and scheduled castes. The State Government have, over the a last decade and/half of planning, mode strenuous efforts to develop its economy so as to bring it in line with other more advanced parts of the country. These have not met with success chiefly due to lack of the requisite The continuance of such an unsatisfactory state of affairs is not in the interest of this State or of the country as a whole.
Government of Madhya Pradesh
Planning and Development Department
Keywords: Memorandum; Agriculture; Land Development; Minor Irrigation; Veterinary; Animal Husbandry; Dairying; Milk Supply; Fisheries; Forest Conservation; Soil Conservation; Community Development; Panchayats